Surgical strategies for necrotising enterocolitis: a survey of practice in the United Kingdom. Issue 2 (21st February 2005) - Rees, C M; Hall, N J; Eaton, S; Pierro, A
Abstract : Background: Strategies for the surgical management of necrotising enterocolitis are various and controversial. Objective: To characterise variation in surgical management of this disease across the United Kingdom. Methods: Postal survey of 104 consultant paediatric surgeons with a 77% response rate. Results: Duration of antibiotic treatment (median 10 days, range 6–14), time until the start of enteral feeding (median 10 days, range 4–21), and absolute indications for surgery all vary between surgeons. Peritoneal drainage is used by 95% of surgeons. Forty two percent use it in neonates of all weights, whereas 36% restrict its use to those <1000 g. Peritoneal drainage is used for stabilisation by 95% and as definitive treatment by 58%. At laparotomy, operative procedures include diverting jejunostomy, resection and stoma, resection with primary anastomosis, and "clip and drop". All procedures are used in infants of all weights except resection and primary anastomosis, which is used predominantly in larger infants (55% in <1000 g; 77% in >1000g; p  =  0.005). Infants may be considered too unwell for peritoneal drainage by 11% of surgeons compared with 90% for laparotomy (p<0.0001). Conclusions: There is considerable variation in surgical strategies for necrotising enterocolitis. Peritoneal drainage is used by most surgeons, with controversial indications and expectations. The use of resection and primary anastomosis is influenced by the weight of the neonate.